Pengaruh Return On Equity, Current Ratio, Net Profit Margin Debt To Equity Ratio Dan Debt To Asset Ratio Terhadap Return Saham Pada Perusahaan Sektor Perdagangan, Jasa Dan Investasi Yang Terdaftar Di Bursa Efek Indonesia - Merry Christina Situmeang; Forisnani Nazara (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to examine whether return on equity, current ratio, net profit margin, debt to equity ratio and debt to asset ratio have an influence on stock returns in trading, service and investment sector companies listed on the Indonesia Stock Exchange in the 2017-2019 period. .This research is a quantitative research, which uses data from 154 trading, service and investment sector companies listed on the Indonesia Stock Exchange, with a sampling technique using purposive sampling technique and obtained a sample of 60 trading, service and investment sector companies that meet the criteria. The data analysis method in this research is multiple linear regression analysis with classical assumption test. The results of this analysis show that simultaneously return on equity, current ratio, net profit margin, debt to equity ratio and debt to asset ratio have no significant effect on stock returns in trading, service and investment sector companies listed on the Indonesia Stock Exchange in the 2017 period. -2019. Partially the debt to asset ratio and current ratio have a significant effect on stock returns in trading, service and investment sector companies listed on the Indonesia Stock Exchange in the 2017-2019 period. Keywords: Return On Equity, Current Ratio, Net Profit Margin, Debt To Equity Ratio, Debt To Asset Ratio And Stock Return.